Foreign Adoptions in Exterior of the Russian Change Money of 1718–1724 - Vadim Serov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The last phase of Peter’s coinage reform was marked, among others, by the alteration of all coin denomination appearances, specifically small ones. The reasons for this did not receive a clear explanation in the specialized literature, and the question of the origin of the forms of the new coin design was not raised at all. The article asks these questions, and it offers a historical reconstruction of novelties in the minor coins exterior of 1711–1724. The analysis of Russian and foreign numismatic material gives any possibility to conclude about the elaboration and introduction of a new design concept in this period, which was distinguished by the more simplicity of coin images. Comparing the exterior’s details of new Russian coins with foreign ones does point to the most probable sources and forms of the adoption. Conclusions. The change of the concept of coin appearance began in 1711 and finished in 1724. As a result, small denominations forfeited their long legends and bulky images. Each adoption was targeted to a concrete part of coin space; it was selected by Peter’s choice and taste. This explains both why the concept of the design was realized so long and why the sources of adoption were so numerous – from countries in Europe and Asia.